( E )-4-Methoxy- N ′-[(6-methyl-4-oxo-4 H -chromen-3-yl)methylidene]benzohydrazide monohydrate - Ishikawa, Yoshinobu; Watanabe, Kohzoh (Acta crystallographica. Section E, Structure reports online, 2014)
In the title hydrate, C 19 H 16 N 2 O 4 ·H 2 O, the 4 H -chromen-4-one segment is slightly twisted, with a dihedral angle between the two six-membered rings of 3.30 (5)°. The dihedral angles between the plane of the pyranone ring and the hydrazide plane and between the planes of the pyranone ring and the benzene ring of the p -methoxybenzene unit are 26.69 (4) and 2.23 (3)°, respectively. The molecule is connected to the solvent water molecule by an N—H...O hydrogen bond. In the crystal, there are π–π stacking interactions between centrosymmetrically related pyranone rings [centroid–centroid distance = 3.5394 (9) Å], as well as bridges formed by the water molecules via O—H...O hydrogen bonds.